Overview of 5-ASA in Therapy of Inflammatory Bowel Disease - CN Williams (Canadian Journal of Gastroenterology)
There are two forms of 5-aminosalicylic acid (5-ASA) drug delivery. First, a pro-drug form in which 5-ASA, the active principal, is attached to a c.arrier molecule and released in the intestine by bacterial cleavage. An example of this is sulfasalazine, originally developed in the 1940s and found to be effective, cheap, but limited by side effects due to the sulfapyridine component. The second drug delivery system depends on an enteric coating for delayed pH-dependent release or for a timed-released mechanism. 5-ASA inhibits 5-lipoxygenase, modulates leukocyte function and inhibits soluble mediator release, and is an effective scavenger action of free oxygen radicals, the relative importance of which is unknown. The multiplicity of action is probably its strength because drugs that have only one of these actions are relatively ineffective in inflammatory bowel disease. 5-ASA compounds are effective in treating mild to moderate acute ulcerative colitis and in maintaining remission, and are equivalent to sulfasalazine in this regard. 5-ASA used topically in enema or suppository form is highly efficient in both acute disease and in maintaining remission. 5-ASA is also effective in active Crohn’s disease, but not as effective as in maintenance therapy compared with ulcerative colitis. The pro-drugs tend to have more side effects. Slow release compounds are well tolerated with few side effects, allowing increases to effective dosage. In patients intolerant of sulfasalazine, switching to a 5-ASA preparation usually results in tolerance and therapeutic benefit, with an occasional allergic reaction to the 5-ASA molecule limiting its use.